A novel purification method of activated carbon-supported carbon nanotubes using a mixture of Ca(OH)2 and KOH as the ablation agent. Issue 2 (4th January 2021) - Hu, Yongjie; Zhang, Linlin; Guo, Qixun; Zheng, Zhifeng; Liu, Yunquan; Ye, Yueyuan; Li, Shuirong; Jia, Xingyong; Wang, Duo
Abstract : Transition metals (Fe, Co, Ni) supported on activated carbons with different pore diameters (<2 nm, 10 nm, 50 nm) to synthesize carbon nanotubes (CNTS) are first investigated in this study. Abstract : Transition metals (Fe, Co, Ni) supported on activated carbons with different pore diameters (<2 nm, 10 nm, 50 nm) to synthesize carbon nanotubes (CNTS) are first investigated in this study. Through several characteristic analyses, Ni supported on 50 nm activated carbon is verified to be the most efficient catalyst among the samples for CNT growth. The optimum conditions for CNT growth are at a growth temperature of 750 °C with a reaction time of 45 min. Furthermore, a novel purification method for CNTs is proposed, in which KOH and Ca(OH)2 powder are pre-mixed with the crude CNTs and CO2 and N2 gas are introduced into this mixture. When KOH and Ca(OH)2 powder are used at a ratio of 2 : 1 under the atmosphere of CO2 and N2 at the temperature of 750 °C for 1 h, almost all of the amorphous carbon is ablated. Compared with KOH powder, the addition of Ca(OH)2 not only advances the ablation effect, but reduces the damage to CNTs.